Perovskite polariton parametric oscillator - Wu, Jinqi (2022)
Optical parametric oscillators (OPOs) have been widely applied in spectroscopy, squeezed light, and correlated photons, as well as quantum information. Conventional OPOs usually suffer from a high power threshold limited by weak high-order nonlinearity in traditional pure photonic systems. Alternatively, polaritonic systems based on hybridized exciton-photon quasi-particles exhibit enhanced optical nonlinearity by dressing photons with excitons, ensuring highly nonlinear operations with low power consumption. We report an on-chip perovskite polariton parametric oscillator with a low threshold. Under the resonant excitation at a range of angles, the signal at the ground state is obtained, emerging from the polariton-polariton interactions at room temperature. Our results advocate a practical way toward integrated nonlinear polaritonic devices with low thresholds.